2008
DOI: 10.1590/s1413-86702008000400008
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection in immunocompromised patients

Abstract: Occult hepatitis B infection is characterized by hepatitis B virus (HBV) DNA in the serum in the absence of hepatitis B surface antigen (HBsAg). We assessed occult HBV infection prevalence in two groups of immunocompromised patients (maintenance hemodialysis patients and HIV-positive patients) presenting HBsAgnegative and anti-HBc positive serological patterns, co-infected or not by HCV. Thirty-four hemodialysis anti-HIV negative patients, 159 HIV-positive patients and 150 blood donors who were anti-HBc positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
3
19
0
3
Order By: Relevance
“…In HIV subjects a strong association between OBI and HCV infection has been observed in several studies [28,101,[104][105][106] . In contrast, Jardim et al [107] reported no significant difference in the rate of OBI in HIV-positive patients with or without HCV coinfection.…”
Section: Epidemiology Of Obi In Hiv-positive Subjectsmentioning
confidence: 90%
“…In HIV subjects a strong association between OBI and HCV infection has been observed in several studies [28,101,[104][105][106] . In contrast, Jardim et al [107] reported no significant difference in the rate of OBI in HIV-positive patients with or without HCV coinfection.…”
Section: Epidemiology Of Obi In Hiv-positive Subjectsmentioning
confidence: 90%
“…Among hemodialysis patients, this rate ranges 0-58% in countries such as Canada, Turkey, Italy, Greece, Spain, Iran, and Brazil 2,[12][13][14][15][16][17][18][19] . In Brazil, data on the frequency of occult HBV infection among hemodialysis patients are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, data on the frequency of occult HBV infection among hemodialysis patients are scarce. Jardim 19 Nonetheless, detecting such patients in hemodialysis clinics is of prime importance for avoiding dissemination of the virus inside these units, given that patients with unidentified occult HBV may transmit this infection to other patients as they undergo their treatment alongside other hemodialysis patients who are susceptible to HBV. The repeated exposure to body fluids during dialysis procedures predisposes dialysis patients to nosocomial transmission of HBV 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Some of the differences are explained by the individual prevalence of HIV and HBV in the different populations studied. Although there are reports from central and south America [17][18][19][20][21][22] , the majority of the studies are from regions of Africa, India and the Far East, regions where the prevalence of both HIV and HBV is high [23][24][25][26][27] . Differences also arise from the type of high-risk group to which the co-infection patients studied belong (e.g., hemodialysis patients, homosexuals, intravenous drug users).…”
Section: Prevalencementioning
confidence: 99%
“…Furthermore, the available data suggest seronegative patients have a different clinical evolution and should therefore be evaluated separately. Another factor that is common in HIV patients and that is known to affect [46] Iran 3 (13.6) 2 (9.1) ND 1 (4.5) Bagaglio et al [47] Italy 9 (31.0) 9 (31.0) ND ND Bell et al [48] Africa [51] Spain 6 (2.4) 2 (0.8) 4 (1.6) ND Filippini et al [13] Italy 17 (20.0) 11 (12.8) 3 (3.5) 3 (3.5) Firnhaber et al [23] Africa 38 (88.4) 38 (88.4) ND ND Gupta et al [30] India 24 (45.3) 13 (24.5) 11 (20.8) ND Hakeem et al [52] Scotland 2 (2.8) 2( 2.9) ND ND Jardim et al [19] Brazil 8 (5.0) 2 (1.3) 6 (3.8) ND Khamduang et al [35] Thailand 47 (23.5) 47 (23.5) ND ND Liang et al [53] Taiwan 3 (2.3) 3 (2.3) ND ND Lo Re et al [54] United States 17 (10.0) 10 (5.6) 7 (3.9) ND Loustaud-Ratti et al [55] France [24] Africa 51 (10.0) 51 (11.8) ND ND Neau et al [58] France 1 (0.6) 1 (0.6) ND ND Nebbia et al [59] England 48 (14.0) 48 (14.0) ND ND Opaleye et al [25] Nigeria 21 (11.2) 8 (4.3) 9 (4.8) 2 (1.1) Panigrahi et al [26] India 12 (10.7) 9 (8.0) 3 (2.7) ND Santos et al [20] Brazil 16 (15.8) 2 4 (4.0) 12 (11.9) ND Sen et al [27] India 1 (5.6) 2 1 (5.6) ND ND Shire et al [60] United States 4 (10.5) 4 (10.5) ND ND Shire et al [61] United States 12 (30.2) 3 (7.0) 5 1 (11.6) 5 (11.6) Sucupira et al [21] Brazil 6 (18.8) 2 3 (9.4) 3 (9.4) ND Torres Barranda et al [22] Mexico 7 (18.4) 1 (2.6) 1 (2.6) 5 (13.2) Tramuto et al [62] Italy 24 (5.9) 8 (2.0) 7 1 (1.7) 9 (2.2) Tsui et al [63] United States 8 (2.0) 8 (2.0) ND ND 1 In some studies the anti-HBsAg positive group was also included; 2 Prevalence calculated using the reported data; anti-HBsAg+, antibodies against hepatitis B surface antigen positive; anti-HBcAg+ antibodies against hepatitis B core antigen positive. Prevalence (%) were included for each group of patients studied according the HBV serological markers (Anti-HBsAg-/anti-HBcAg+, Anti-HBsAg+/anti-HBcAg+, Anti-HBsAg-/anti-HBcAg-).…”
Section: Clinical Significancementioning
confidence: 99%